2010
DOI: 10.1029/2010jd014479
|View full text |Cite
|
Sign up to set email alerts
|

Terdiurnal tide in the extended Canadian Middle Atmospheric Model (CMAM)

Abstract: [1] We use the extended Canadian Middle Atmosphere Model (CMAM), a general circulation model (GCM), to investigate the nature of the terdiurnal tide. Temperature and horizontal winds from a model run are analyzed to delineate the character of this tide for zonal wave numbers s = −5 to +5. Descriptions of the annual mean amplitudes, seasonal variations, and total tide superposed from the migrating and 10 nonmigrating components are provided. The amplitudes and vertical wavelengths of the various components and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
76
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(91 citation statements)
references
References 51 publications
14
76
1
Order By: Relevance
“…This was followed by a paper which described the physical parameterizations and presented a zonal mean climatology and energy budget from the extended CMAM (Fomichev et al, 2002). Nonmigrating tides generated by the CMAM and observed in the MLT region were discussed by Ward et al (2005), and papers by Du et al (2007) and Du and Ward (2010) showed that the semidiurnal and terdiurnal tidal signatures were realistic. McLandress et al (2006) analyzed the large-scale dynamics of the MLT region simulated by the model.…”
Section: Model Descriptionmentioning
confidence: 99%
“…This was followed by a paper which described the physical parameterizations and presented a zonal mean climatology and energy budget from the extended CMAM (Fomichev et al, 2002). Nonmigrating tides generated by the CMAM and observed in the MLT region were discussed by Ward et al (2005), and papers by Du et al (2007) and Du and Ward (2010) showed that the semidiurnal and terdiurnal tidal signatures were realistic. McLandress et al (2006) analyzed the large-scale dynamics of the MLT region simulated by the model.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Taylor et al (1999) reported a large amplitude terdiurnal (8-h) tide in temperature data from an airglow imager. Younger et al (2000) and Du and Ward (2005) presented the global and seasonal structure of the terdiurnal tide in horizontal winds observed by HRDI and WINDII, respectively. Modeling studies by Smith and Ortland (2001) and Akmaev (2001a) indicated that the mean terdiurnal tide is primarily forced by solar heating although generation by nonlinear interaction between diurnal and semidiurnal migrating tides also contributed.…”
Section: Semidiurnal and Higher-frequency Tidesmentioning
confidence: 99%
“…The terdiurnal tide generally reaches smaller amplitudes, but can nevertheless be significant (e.g. Teitelbaum et al, 1989;Younger et al, 2002;Du and Ward, 2010).…”
Section: R N Davis Et Al: Mesospheric Tides Over Ascension Islandmentioning
confidence: 99%